MutMap Approach Enables Rapid Identification of Candidate Genes and Development of Markers Associated With Early Flowering and Enhanced Seed Size in Chickpea (Cicer arietinum L.) - Manchikatla, Praveen Kumar; Kalavikatte, Danamma; Mallikarjuna, Bingi Pujari; Palakurthi, Ramesh; Khan, Aamir W.; Jha, Uday Chand; Bajaj, Prasad; Singam, Prashant; Chitikineni, Annapurna; Varshney, Rajeev K.; Thudi, Mahendar (Frontiers in Plant Science, 2021)
Globally terminal drought is one of the major constraints to chickpea (Cicer arietinum L.) production. Early flowering genotypes escape terminal drought and the increase in seed size compensates for yield losses arising from terminal drought. A MutMap population for early flowering and large seed size was developed by crossing the mutant line ICC4958-M3-2828 with wild type ICC 4958. Based on the phenotyping of MutMap population, extreme bulks for days to flowering and 100 seed weight were sequenced using Hi-Seq2500 at 10X coverage. On aligning 47.41 million filtered reads to the CDC Frontier reference genome, 31.41 million reads were mapped and 332,395 SNPs were called. A reference genome assembly for ICC 4958 was developed replacing these SNPs in particular positions of the CDC Frontier genome. SNPs specific for each mutant bulk ranged from 3993 to 5771. We report a single unique genomic region on Ca6 (between 9.76 and 12.96 Mb) harbouring 31, 22, 17 and 32 SNPs with a peak of SNP-index = 1 for low bulk for flowering time, high bulk for flowering time, high bulk for 100 seed weight and low bulk for 100 seed weight, respectively. Among these, 22 SNPs are present in 20 candidate genes and had moderate allelic impact on the genes. Two markers, Ca6EF10509893 for early flowering and Ca6HSDW10099486 for 100 seed weight, were developed and validated using the candidate SNPs. Thus the associated genes, candidate SNPs and markers developed in this study are useful for breeding chickpea varieties that mitigate yield losses under drought stress.